KEPATUHAN KUNJUNGAN ULANG IBU NIFAS DENGAN REMINDER "BUFAS"Â DI PUSKESMAS SUMBERJO KABUPATEN KEDIRI - Rahmawati, Rahajeng Siti Nur; Krisdiana, Ika Yuli; Suwoyo, Suwoyo (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
The postpartum period is a critical period for the mother, about 60% of maternal deaths due to pregnancy occur after delivery, and 50% of postpartum deaths occur within the first 24 hours of labor. Based on the results of the initial survey conducted at the Community Health Center Sumberjo, there were 3 mothers from 5 mothers interviewed who did not make a postpartum re-visit, because they forgot the schedule for the next visit. This study is the development of an android-based reminder application that is used to improve maternal compliance in performing postpartum re-visits. The purpose of this study was to determine the Compliance of Postpartum Mother Re-Visit with Reminder BUFAS in the Community Health Center Sumberjo Kediri. This study uses the Survey Cohort, with a sample of 10 respondents taken by purposive sampling. Data analysis used the descriptive. From the analysis of the data obtained from 10 postpartum mothers almost all (90%) adhered to postpartum repeat visits. After being analyzed, it can be concluded that the compliance of the return visit of the postpartum mother was almost as complete as the second visit after the application was given. Based on the description above, was expected that the respondent can adhere to the visit during the postpartum period according to the program that has been set. Keywords: Reminder Application, Compliance, Postpartum Revisit, Postpartum Period.